Lean Six Sigma for engineers and managers : with applied case studies - Franchetti, Matthew J. (CRC Press, Taylor & Francis Group, 2015)
"This book introduces Lean Six Sigma (LSS) to engineers and managers interested in implementing LSS at their organizations. The book provides a detailed roadmap and industry examples to aid readers in understanding and implementing the LSS system. This book discusses the LSS process to define improvement needs, measure current business performance, analyze performance results using statistical tools, improve business and financial results, and control peak business performance"--Resumé vydavatele
Keywords: Six Sigma (metoda); Six Sigma (Quality control standard); případové studie; příručky; case studies; handbooks, manuals, etc